The Application of Seaweed Polysaccharides and Their Derived Products with Potential for the Treatment of Alzheimer’s Disease - Sarah Bauer; Weihua Jin; Fuming Zhang; Robert J. Linhardt (Marine Drugs, 2021)
Neurodegenerative diseases are among the most widespread diseases affecting humans, and the number of patients is only rising. Seaweed polysaccharide extracts show significant neuroprotective and reparative activities. Seaweed polysaccharides might provide the next big breakthrough in neurodegenerative disease treatment. This paper reviews the applications of seaweed polysaccharides as potential treatments of neurodegenerative diseases. The particular focus is on fucoidan, ulvan, and their derivatives as potential agents to treat Alzheimer’s disease. This review provides a critical update on the progress in this important research area.